2021
DOI: 10.1111/jfpp.15309
|View full text |Cite
|
Sign up to set email alerts
|

Gamma irradiation treatment of minimally processed kiwi fruit to maintain physicochemical quality and prevent microbial proliferation during refrigerated storage

Abstract: Mature kiwi after minimal processing were treated with 0.5–2.0 kGy gamma irradiation to monitor changes in quality parameters under refrigerated conditions (3 ± 1°C, RH 85%) for 16 days. The results revealed that treatment of 2.0 kGy proved helpful in delaying onset of surface browning, reducing the polyphenol oxidase activity and preserving the original color of samples till 16 days. Dose dependent decrease in polyphenol oxidase activity and surface browning was observed in kiwi samples. Control samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In contrast, gamma irradiated 'Hayward' kiwifruit at high doses (>1000 Gy) had lower L* values (darker fruit) than control (nonirradiated) during the early storage period, but a radiation dose of 3000-Gy fruits had higher surface L* values than 1000-and 2000-Gy irradiated fruits (Kim and Yook 2009). Also, L* values increased with doses up to 2000 Gy in minimally processed kiwifruit stored for 12 d at 3 C, indicating a dose-dependent decrease in flesh surface browning (Hussain et al 2021).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, gamma irradiated 'Hayward' kiwifruit at high doses (>1000 Gy) had lower L* values (darker fruit) than control (nonirradiated) during the early storage period, but a radiation dose of 3000-Gy fruits had higher surface L* values than 1000-and 2000-Gy irradiated fruits (Kim and Yook 2009). Also, L* values increased with doses up to 2000 Gy in minimally processed kiwifruit stored for 12 d at 3 C, indicating a dose-dependent decrease in flesh surface browning (Hussain et al 2021).…”
Section: Resultsmentioning
confidence: 94%
“…However, for kiwifruit treated with 1000to 3000-Gy gamma irradiation, sensory panelists preferred fruit treated with 3000 Gy over the control (nonirradiated) 'Hayward' fruit (Kim and Yook 2009). Also, minimally processed kiwifruit treated with 2000-Gy radiation had higher overall acceptability based on texture and color, relative to nonirradiated samples (Hussain et al 2021). This indicates that kiwifruit can maintain sensory quality at doses above those used for quarantine treatment and will be acceptable to consumers.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ozone, gamma irradiation, and cold plasma have been applied in the inactivation of enzymes (Hussain et al., 2021; Mayookha et al., 2023). Ozone, a triatomic form of oxygen, has been widely used as an antimicrobial agent in drinking water.…”
Section: Intervention Strategies For O‐quinone and O‐quinone‐induced ...mentioning
confidence: 99%
“…-Radiation may reduce the lignification of immature bamboo shoots and the lignin concentration by 12.5% after 28 days of storage at 2 °C [17]. In many foods, particularly minimally processed foods, the use of -radiations for fruit and vegetable preservation has been proven to be beneficial in inactivating and eliminating spoilage and foodborne bacteria [18]. Numerous studies have shown that -irradiation treatment successfully exterminates the microbes responsible for decay from fresh-cut fruits and vegetables without degrading the quality overall [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, -irradiation's impact on Dendrocalamus hamiltonii bamboo shoots has not yet been reported. Therefore, our current study demonstrated the impact of -radiation on post-harvest retention of storage quality and prevention of microbial proliferation of Dendrocalamus hamiltonii shoot by assessing the physicochemical and microbial parameters 4), [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] including sensory evaluation at varied storage time.…”
Section: Introductionmentioning
confidence: 99%